PERANCANGAN SISTEM INFORMASI DATA SISWA DAN GURU PADA TK DARMA BAKTI DEPOK BERBASIS JAVA - Gita Anggeli Septiana Lestari; Thomas Afrizal; Mahyudi Mahyudi (Pusat Riset dan Inovasi Nasional, 2022)
Darma Bakti Kindergarten is one of the levels of early childhood education in the form of formal education that provides educational programs for children with an age range of 4-6 years. Data collection or data management, especially student and teacher data, are currently partly not computerized, namely still recording data in ledgers and some using computerization, namely using Microsoft Word and Microsoft Excel. However, it allows data in the ledger to be prone to loss and tearing, data input errors, repetition of data input (Data Double), loss of data, data searches that take a long time, ineffective data reporting because the reported data process must be typed one by one. first. The purpose of this research is to build a data information system for students and teachers using the Java programming language and MySQL database. At this writing the author uses qualitative methods, and the information system design method used is the waterfall method. With the design of this information system, the problem of data collection in TK Darma Bakti Depok can be resolved.